Cost Effectiveness of Selected Post Harvest Pod Handling Techniques Against Damage, Mouldiness and Aflatoxin Contamination of Shelled Groundnut in Ghana (Journal of Science and Technology, 2016)
Some post harvest pod handling methods were evaluated at Ejura and at KNUST, Kumasi to determine the costs and effectiveness of the methods in minimising post harvest damage, mouldiness and aflatoxin (AF) contamination of shelled groundnut. The study was conducted in 2002 (dry season) and repeated in 2003 (wet season). Four treatments were imposed on pods from 180 m2 plots at harvest. The treatments were (i) inverted windrowing (1wk) followed by drying of the pods on mats (3wk) (ii) random windrowing (1wk) followed by drying of the pods on mats (3wk) (iii) stripping and drying of pods on mats (4wk) and (iv) storage of pods without drying (control). Costs involved in carrying out the treatments were estimated. Fungi associated with the kernels and AF levels were also determined at harvest and at 4 weeks. In both seasons, Aspergillus niger was the most common fungus associated with kernels at harvest and after the 4 wk pod handling periods. Aspergillus flavus was also encountered at both periods. When pods were dried for 4 wk, the amounts of damaged/mouldy ones that were rejected were low (2.7-13.1%; av. 8.6 %) compared with undried pods where 18.9-25.94% (av. 22.08%) were rejected. Aflatoxins were not detected in kernels at harvest and generally, dried pods had lower levels of AFs (0 - 0.7µg/kg) than the undried control pods (7278.1µg/kg). Visibly healthy pods sorted from the dried lots had kernel AF levels of 0.2 - 0.6µg/kg which were similar to the 0 - 0.7µg/kg levels associated with the unsorted lots. Sorting, however, cost an extra ¢31,354/100 kg lot (¢8,200 = $ US1), making the practice uneconomical for well dried pods. Total cost of pod drying up to 4 wk was the same for the random and the inverted windrowed crops (¢89,980/100 kg pod) but was ¢95,440 when pods were dried on mats immediately after stripping. When pods were not dried, cost of handling was ¢69,600/100 kg pods but due to the high AF contamination (7278.1µg/kg), kernels from such pods constitute total loss. Thus, both windrow and mat drying of groundnut pods are cost effective in controlling damage/mouldiness and AF contamination but costs are lower when windrowed.